2023
DOI: 10.3390/antiox12030706
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the H2O2 Biosensor roGFP-Tpx1.C169S in Fission and Budding Yeasts and Jurkat Cells to Compare Intracellular H2O2 Levels, Transmembrane Gradients, and Response to Metals

Abstract: Intracellular hydrogen peroxide (H2O2) levels can oscillate from low, physiological concentrations, to intermediate, signaling ones, and can participate in toxic reactions when overcoming certain thresholds. Fluorescent protein-based reporters to measure intracellular H2O2 have been developed in recent decades. In particular, the redox-sensitive green fluorescent protein (roGFP)-based proteins fused to peroxiredoxins are among the most sensitive H2O2 biosensors. Using fission yeast as a model system, we recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…ROS are very short-living molecules, and detecting ROS in living systems is complex and requires new developments. In the present Special Issue, Cubas et al [12] developed a susceptible H 2 O 2 sensor capable of quantitatively analyzing the ratio of extracellular peroxides to intracellular peroxides across the plasma membrane. They found that this ratio is approximately 300:1 and remains similar in different species.…”
Section: Pleiotropic Actions Of Ros and Antioxidantsmentioning
confidence: 99%
“…ROS are very short-living molecules, and detecting ROS in living systems is complex and requires new developments. In the present Special Issue, Cubas et al [12] developed a susceptible H 2 O 2 sensor capable of quantitatively analyzing the ratio of extracellular peroxides to intracellular peroxides across the plasma membrane. They found that this ratio is approximately 300:1 and remains similar in different species.…”
Section: Pleiotropic Actions Of Ros and Antioxidantsmentioning
confidence: 99%